2018
DOI: 10.1111/cas.13716
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death ligand‐1 protein expression and CD274/PD‐L1 gene amplification in colorectal cancer: Implications for prognosis

Abstract: Programmed cell death ligand‐1 (PD‐L1) detection assays have not been standardized for patients with colorectal cancer, and the prognostic value of PD‐L1 expression is unclear. We compared the PD‐L1 expression patterns in colorectal cancer samples using various immunohistochemical assays using 3 primary PD‐L1 antibodies (assay 1, MIH1; assay 2, E1L3; and assay 3, 22C3) and investigated the prognostic implication of PD‐L1 expression using each. Additionally, PD‐L1 gene amplification was evaluated using FISH. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 31 publications
(61 reference statements)
0
41
0
Order By: Relevance
“…17 Among four studies on CRC, Zhu et al 18 reported that CRC patients that expressed PD-L1 had better survival rates. Lee et al 19 recently reported similar results. In our study, PD-L2 expression was significantly correlated with better survival.…”
Section: P-valuementioning
confidence: 52%
See 1 more Smart Citation
“…17 Among four studies on CRC, Zhu et al 18 reported that CRC patients that expressed PD-L1 had better survival rates. Lee et al 19 recently reported similar results. In our study, PD-L2 expression was significantly correlated with better survival.…”
Section: P-valuementioning
confidence: 52%
“…Lymphocytic infiltrations are frequently identified in the colorectum, and the prognostic implication of TILs in CRC is well understood. [20][21][22] Although TILs are significantly correlated with PD-L1 expression, 19 the correlation between PD-L2 expression and TILs has not been fully elucidated in CRC. Masugi et al 2 studied the correlation between PD-L2 expression and lymphocytic reaction in CRC.…”
Section: P-valuementioning
confidence: 99%
“…Regarding the value of PD-L1 as a prognostic marker of cancer evolution, recent data have shown that increased PD-L1 expression is associated with unfavourable outcome in various cancers, but there are conflicting reports regarding its prognostic value in others, such as colorectal cancer [26]. This discrepancy can be attributed to technical issues but also to the origin and form of PD-L1 investigated.…”
Section: The Pd-1/pd-l1 Immune Checkpoint In Melanoma Aggressivenessmentioning
confidence: 99%
“…For instance, expression of PD-L1 by tumour cells and by tumour-infiltrating immune cells has opposite effects on colorectal cancer aggressiveness and metastasis [26]. Moreover, studies investigating the role of PD-L1 on cancer development should distinguish membrane PD-L1 expressed by tumour and immune cells from plasma sPD-L1 and other circulating PD-L1 sources [27].…”
Section: The Pd-1/pd-l1 Immune Checkpoint In Melanoma Aggressivenessmentioning
confidence: 99%
“…Therefore, the copy number of dose-sensitive genes is more likely to be used as a driver gene in cancer. Some of the dosage-sensitive genes (DSGs) such as CD274/PD-L1 gene amplification (Lee et al, 2018b), fibroblast growth factor 1 amplification (Bae et al, 2019), RING-Finger Protein 6 amplification (Steinman et al, 1979), have been shown to be associated with poor prognosis, suggesting DSGs can also be considered as prognostic markers.…”
Section: Introductionmentioning
confidence: 99%